Zeros of Random Functions Generated with de Branges Kernels - Antezana, Jorge Abel (2017)
We study the point process given by the set of real zeros of random series generated with orthonormal bases of reproducing kernels of de Branges spaces. We find an explicit formula for the intensity function in terms of the phase of the Hermite-Biehler function generating the de Branges space. We prove that the intensity of the point process completely characterizes the underlying de Branges space.